Reflections from psychoanalysis on justice, law and legality in Peru - Franco Valdivia, Rocío (2016)
This article proposes a reflection on the irrational aspects of justice and legality that remain veiled in the debate on the difficulties of judicial reform processes in our region and which are expressed harshly in gender violence. Psychoanalytic contributions on culture state that the existence of the unconscious (the instinctual life of the subject) is that which enables the establishment of the law. From this perspective, conflict is inherent in human beings and the anxieties it arouses cannot be bypassed or denied. Therefore, the establishment of limits and a healthy expression of aggression depend on the internal construction of legality in the subject. On the intersubjective level, the mismatch between the expectations of the population and justice operators is associated with the confusion between social reality and the real (Lacan), generating a basic misunderstanding to be solved. As a method, fundamental psychoanalytic concepts are employed and situations of violence against women from Peruvian rural communities are discussed. The paper concludes that it is essential to any process of change or reform to work around the elaboration of anxieties that block the task in institutions and groups. This work facilitates access to justice, while generating new knowledge in this field.